Trolleybus power system for operation with AC or DC distribution networks - Melo, G. A. [UNESP] (2010)
This paper presents the development and experimental analysis of a special input stage converter for a Trolleybus type vehicle allowing its operation in AC (two wires, single-phase) or DC distribution networks. The architecture of proposed input stage converter is composed by five interleaved boost rectifiers operating in discontinuous conduction mode. Furthermore, due to the power lines characteristics, the proposed input power structure can act as AC to DC or as DC to DC converter providing a proper DC output voltage range required to the DC bus. When operation is AC to DC, the converter is capable to provide high power factor with reduced harmonic distortion for the input current, complying with the restrictions imposed by IEC 61000-3-4 standard. Finally, the main experimental results are presented in order to verify the feasibility of the proposed converter, demonstrating the benefits and the possibility for AC feeding system for trolleybus type vehicle. © 2010 IEEE.